EDUKASI DIIT DENGAN MEDIA BOOKLET DALAM MENINGKATKAN KEPATUHAN DIIT DAN KADAR GULA DARAH PADA PASIEN DM TIPE II - Nita Riany Momongan; Olga Lieke Paruntu; Stevina Y Barangmanise; Novry Christofel Takahipe (POLTEKKES KEMENKES MANADO, 2021)
Diabetes Mellitus is a metabolic disease characterized by high blood sugar levels (hyperglycemia) as a result of insufficient insulin secretion, impaired insulin activity, or both, DM can cause complications if not managed properly, good DM management behavior for patients needs to be done by maintaining adherence to nutritional therapy and good meal planning to improve blood sugar levels. This study aims to determine the effectiveness of diet education with booklet media on diet compliance and blood sugar levels in type II DM patients at RSU GMIM PANCARAN KASIH MANADO. The type of research in this study was pre experimental design using one group pre-test-post test. This study used purposive sampling technique with a sample size of 16 respondents, data collection using a questionnaire and analyzed using the Paired t test. The results showed that there were differences in dietary adherence and blood sugar levels before and after being educated with booklet media in type II dm patients at RSU GMIM Pancaran Kasih Manado with the value of statistical testing using the paired t test with a significance level of 0.000 (p <0.05). The conclusion of the effectiveness of dietary education with booklet media on dietary adherence and reduction of fasting blood sugar levels in DM type II patients at rsu GMIM Pancaran Kasih Manado experienced significant changes before and after being educated with booklet media.